Analysis of Johan Galtung's Concept of International Peace in the 1967 Outer Space Treaty - Tandungan, Edmondus Sadesto; Salim, Andre (International Journal of Law Reconstruction, 2024)
The 1967 Outer Space Treaty is the legal basis for every country to carry out space exploration. The formation of the Outer Space Treaty in 1967 was a step forward as a basis for the use of outer space for peaceful purposes. Johan Galtung's concept of international peace can be a reference in analyzing the concept of international peace in the 1967 Outer Space Treaty. The aim of this writing is to analyze the application of Johan Galtung's concept of international peace in the 1967 Outer Space Treaty. This type of research is normative legal research that examines the Outer Space Treaty. Space Treaty 1967 and various concepts in international law. The data used is secondary data in the form of primary legal materials and secondary legal materials. The primary legal material used is the provisions on the use of outer space in the 1967 Outer Space Treaty and the UN Charter, while the secondary legal material consists of various literature related to the topic under study. The data obtained was then analyzed qualitatively using deductive thinking methods. The research results show that the correlation between Johan Galtung's concept of international peace in the 167 Outer Space Treaty can be seen from the stages of peace, namely peacemaking, peacekeeping, and peacebuilding.